Poleward moving auroral forms (PMAFs) revisited: responses of aurorae, plasma convection and Birkeland currents in the pre- and postnoon sectors under positive and negative IMF B y conditions - Sandholt, P. E.; Farrugia, C. J. (HAL CCSD, 2007)
International audience Using five case studies, we investigate the dynamical evolution of dayside auroral precipitation in relation to plasma convection, classifying it by the IMF B y component and position with respect to noon. Auroral observations were made by meridian scanning photometers (MSPs) and an all-sky camera (ASC) in Ny Ålesund, Svalbard at 76° MLAT, while the spatial structure of the ionospheric plasma convection is inferred from SuperDARN radars and ion drift observations from spacecraft in polar orbit. The IMF configuration of major interest here is one pointing southward and with a dominant east-west component. Our emphasis is on the auroral phenomenon of PMAFs (poleward moving auroral forms), which are ionospheric signatures of pulsed reconnection at the magnetopause. We distinguish between PMAFs/prenoon and PMAFs/postnoon. These two activities are found to be separated by an auroral form around noon with attenuated emission at 630.0 nm. We document for the first time that this "midday gap aurora" appears in the form of a midday auroral brightening sequence (MABS). We study the PMAF activity consisting of an initial brightening phase and the later stages of PMAF evolution in relation to plasma convection cells, flow vorticity, and precipitation boundaries in the prenoon and postnoon sectors for both B y polarities. Flow channels (PIFs) associated with PMAFs are strengthened by polarization effects at auroral boundaries. Addressing the implications of our proposed, extended perspective on dayside auroral morphology under southeast/west IMF for M-I coupling associated with pulsed magnetopause reconnection (FTEs), we draw inferences on the MLT-dependent geoeffectiveness (Birkeland current/auroral intensity) of magnetopause FTEs (subsolar region versus flanks).